The Relationship Between the Intensity of Muraja'ah and the Effectiveness of Time Management with the Evaluation of Al-Qur'an Memorization of Students - Nurhadani Nasution; Nurmawati Nurmawati; Harun Al Rasyid (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to determine the relationship between the intensity of muraja‟ah and time management effectiveness with the evaluation of Qur‟anic memorization among female students at the Tahfizh Ulumul Qur’an Islamic Boarding School in Medan. This is a field study employing a quantitative approach. The sample consisted of 100 female students from the Madrasah Aliyah program at the Tahfizh Ulumul Qur’ an Islamic Boarding School in Medan. Data collection techniques included questionnaires, documentation, and interviews. Data analysis techniques utilized linear and multiple regression. The results of this study indicate that the intensity of muroja‟ah has a significant relationship with the evaluation of Quran memorization among students at the Tahfizh Ulumul Qur’an Islamic Boarding School in Medan. This is indicated by a calculated r value greater than the critical r value (0.457 > 0.195), a p-value of 0.000 < 0.005, and a contribution of 20.9%. The effectiveness of time management has a significant relationship with the evaluation of students' Quran memorization at the Tahfizh Ulumul Qur'an Islamic Boarding School in Medan. This is indicated by a calculated r value greater than the critical r value (0.498 > 0.195), and a p-value of 0.000 < 0.005, with a contribution of 24.8%. There is a significant relationship between the intensity of muraja‟ah and the effectiveness of time management, simultaneously with the evaluation of Quran memorization among students at the Tahfizh Ulumul Qur'an Islamic Boarding School in Medan. This is indicated by the calculated F-value being greater than the critical F-value (26.581 > 3.09), and the significance value of 0.000 < 0.005, with a contribution of 35.4%.